150k views
0 votes
What value of x makes the equation 3(x-6) – 8x = -2 + 5(2x + 1) true? Show your work.

User Flau
by
5.8k points

1 Answer

1 vote

9514 1404 393

Answer:

x = -1.4

Explanation:

3(x-6) -8x = -2 + 5(2x + 1)

3x -18 -8x = -2 +10x +5 . . . . . . . eliminate parentheses

-21 = 15x . . . . . . . . . . . . . . add 5x -3 and collect terms

x = -21/15 = -7/5

x = -1.4

__

Check

3(-1.4 -6) -8(-1.4) = -2 +5(2(-1.4) +1) . . . substitute for x

3(-7.4) +11.2 = -2 +5(-2.8 +1)

-22.2 +11.2 = -2 +5(-1.8)

-11 = -2 -9 . . . . . true

User Meson
by
5.7k points